Strategi Pemecahan Masalah Heuristik: Sebuah Metode untuk Merepresentasikan Masalah Matematika dalam Pembelajaran Matematika - Mutia Mutia; Dete Konggoro (Institut Agama Islam Negeri (IAIN) Curup, 2021)
In mathematics, there are two criteria for questions or problems, namely challenging and demanding procedures that are not routine in solving them. The problem is a situation where a person is able to realize the existence of a situation and admit that the situation requires action and resolution that is not easy. By using problem solving strategies, students can make a mathematical representation of the problem, which is one of the abilities in mathematics related to problem solving, reasoning, proof, and communication. Conversely, if we choose the right representation, it will allow us to reach an effective solution to the problem. Heuristic is a strategy used to find and solve a mathematical problem using solving steps. There are many types of heuristic strategies that can be used in learning mathematics to solve problems, but in this study, will be discussed strategies by Mathlin, namely The Analogy Approach, The Means-Ends Heuristic, and The Hill-Climbing Heuristic.